Recent Advances in Broadcast Audio Coding - Popp, Julian; Forster, Christian; Heuberger, Albert; et al. (IEEE BMSB 2013, 2013)
In the last decades there have been major advances in broadcasting technologies as well as a change in consumer behaviour and demands. The on-demand concepts and streaming technology, together with widely available fixed and mobile broadband Internet connections, had an eminent impact on the broadcasters to fit the consumer's needs with respect to content variety, quality and availability. Due to the limited capacity available for broadcasting content, especially over the air, more and more efficient codecs were necessary. This paper will give a short overview of the history of broadcast audio coding and point out which codecs are currently used in the major broadcasting systems, i.e. DVB, DAB and DRM. Recent developments in broadcast audio coding will be presented, focusing on spatial audio object coding and unified speech and audio coding technologies. © 2013 IEE
UnivIS-Import:2015-04-16:Pub.2013.tech.IE.komele.recent
Keywords: Digital Broadcasting; Audio Coding; SAOC; xHE-AAC